Current treatments of rheumatoid arthritis: from the 'NinJa' registry. (July 2012) - Saeki, Yukihiko; Matsui, Toshihiro; Saisho, Koichiro; Tohma, Shigeto
In this review, recent changes in both treatments and outcomes of rheumatoid arthritis (RA) in Japan were analyzed by viewing the National Database of Rheumatic Diseases by iR-net, one of the largest clinical databases for RA patients in Japan. Regarding drug therapy, the use of methotrexate has been continuously increasing and has established a place as an anchor drug in the treatment of RA among other nonbiologic disease-modifying antirheumatic drugs; however, the dosage used is still significantly less compared with that of western countries. In addition to methotrexate, the use of tacrolimus has increased gradually. The most prominent observed change is a rapid increase in the use of biologics, which rose to stardom in the treatment of RA in Japan and western countries. These changes in drug therapy could allow us to control RA disease activity more tightly. In line with this, the outcomes of patients with RA in Japan have been improving continuously, both clinically and functionally. Subsequently, the use of both NSAIDs and corticosteroids has decreased. In addition, overall rates of joint operations related to RA have also decreased; in particular, a significant decrease was noticed in the incidence of joint replacement and synovectomy. Overall, the trends in treatments and subsequent outcomes for RA in Japan have exactly followed those seen in western countries.